Analisis Dimensions dengan Keyword “Tafsir Tematik” menggunakan Bibliometrik - Lindiani Nur Fadhilah (Gunung Djati Conference Series, 2023)
This study aims to analyze the database in the dimensions related to the keyword "Thematic Interpretation" in the dimension. This study uses a quantitative approach with the bibliometric method. The results and discussion of this study present the findings of the exploratory research that has been presented. This study covers research areas, research trends, researchers and places of publication regarding thematic interpretation research. The results of the research show that thematic interpretation studies are still being developed and studied by many experts.